The Role of Semantic Diversity in Word Recognition across Aging and Bilingualism - Johns, Brendan T.; Sheppard, Christine L.; Jones, Michael N.; Taler, Vanessa (Frontiers in Psychology, 2016)
Frequency effects are pervasive in studies of language, with higher frequency words being recognized faster than lower frequency words. However, the exact nature of frequency effects has recently been questioned, with some studies finding that contextual information provides a better fit to lexical decision and naming data than word frequency (Adelman, Brown, & Quesada, 2006). Recent work has cemented the importance of these results by demonstrating that a measure of the semantic diversity of the contexts that a word occurs provides a powerful measure to account for variability in word recognition latency (Jones, Jones, & Recchia, 2012; Johns, et al., 2012; Johns, Dye, & Jones, in press). The goal of the current study is to extend this measure to examine bilingualism and aging, where multiple theories use frequency of occurrence of linguistic constructs as central to accounting for empirical results (Gollan, Montoya, Cera, & Sandoval, 2008; Ramscar, Hendrix, Shaoul, Milin, & Baayen, 2014). A lexical decision experiment was conducted with 4 groups of subjects: younger and older monolinguals and bilinguals. Consistent with past results, a semantic diversity variable accounted for the greatest amount of variance in the latency data. In addition, the pattern of fits of semantic diversity across multiple corpora suggests that bilinguals and older adults are more sensitive to semantic diversity information than younger monolinguals.